Parsimonious: Initiation of Integrated Financial Health Assessment Model in Preventing Company Bankruptcy (Case Study: PT Pos Indonesia (Persero) Period 2018-2020) - Pradana Jati Kusuma; Febrianur Ibnu Fitroh Sukono Putra; Tito Aditya Perdana (TIJAB (The International Journal of Applied Business), 2022)
This study aims to analyze the development of health assessment indicators and the financial health condition of PT Pos Indonesia (Persero). This research used a quantitative approach. The analysis technique used for evaluating the level of financial health referred to the Decree of The Minister of State-Owned Enterprises No. Kep- 100/MBU/2002. The data collection technique used was documentation studies sourced from the annual report of PT Pos Indonesia (Persero) from 2018 through 2020. The results showed that the development of the indicator value of return on equity, return on investment, and cash ratio decreased, while the value of collection periods, the ratio of equity to total assets, and inventory turn over increased. This study also found the fluctuated value of the current ratio and total asset turnover. The financial health assessment in 2018 and 2019 had a healthy predicate. However, in 2020, it had an unhealthy financial health assessment predicate. Therefore, the company needs to have better financial performance to achieve good financial health conditions that will finally affect all stakeholders.